Pelatihan Pengambilan Konten Visual dan Videografi Bagi Siswa SMA 9 Semarang - Jasmine Agam; Wilda Alfina; Citra Yuslaresa; Mita Armevia Putri; Avida Sidabutar; Tika Ristia Djaya (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This activity aims to improve students' abilities in producing interesting and informative visual content through training provided by Communication Science students at Semarang University. The method of this activity is to provide training on documentary video making, video production processes, promotional video making techniques, data collection, and videography. The result of this activity is that students are able to practice the material provided, including practice producing documentary videos and promotional videos as well as being able to practice videography techniques. Apart from that, it also provides benefits for Semarang University lecturers and students as organizers of activities so they can implement their knowledge to the community. Post-training evaluation shows an increase in students' knowledge and skills in creating visual content. The students' positive responses in the form of active participation and high motivation in participating in the training showed high satisfaction and relevance to the material presented, this indicates the success of this training in motivating and developing students' interest in photography, videography and social media.